Additively manufactured unimorph dielectric elastomer actuators: Design, materials, and fabrication - Sikulskyi, Stanislav; Ren, Zefu; Mekonnen, Danayit T.; Holyoak, Aleiya; Srinivasaraghavan Govindarajan, Rishikesh; Kim, Daewon (Frontiers in Robotics and AI, 2022)
Dielectric elastomer actuator (DEA) is a smart material that holds promise for soft robotics due to the material’s intrinsic softness, high energy density, fast response, and reversible electromechanical characteristics. Like most soft robotics materials, DEA can significantly benefit from employing additive manufacturing. This paper presents a study on the modeling and fabrication of unimorph DEA (UDEA), a configuration capable of producing large bending deformation and one of the most suitable to be implemented through 3D printing. Firstly, the UDEA analytical model was derived to describe its static behavior and address essential features for soft actuators. The model allowed to illustrate the effect of each UDEA layer on actuator performance and obtain several figures of merit (FOMs) for simple design optimization and material selection. FOMs have various degrees of complexity depending on considered UDEA design features. Secondly, intending to facilitate research on any 3D printed soft actuators and robotics, this paper demonstrates the fabrication challenges of DEA comprised of commercially available silicones utilizing accessible 3D printing equipment. Materials’ manufacturability, viscosity, and curing are mainly studied to determine their printing handling time. Finally, 3D printing and testing a UDEA validated the developed modeling and fabrication methodologies.